Strength analysis of girder structure on a 6 Ton capacity overhead crane using statics method - Arif, Syaiful (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
An overhead crane is a critical piece of equipment used to move equipment or components both vertically and horizontally. The overhead crane design process requires an accurate calculation and design approach. In this study, the design was conducted using two approaches: manual calculation and finite element method (FEM)-based design simulation. The manual calculations included analysis of components such as the lifting hook, drive system, braking system, truss, and steel rope. The results of the manual analysis were then compared with the FEM simulation results. In this case, the simulation was conducted using ANSYS 17.0 software with a static structural analysis type. The analysis results showed that the stress in the hook component using FEM was recorded at 117.53 N/mm², while the stress in the steel rope reached 135.49 N/mm². The pulley component yielded a stress of 27,845 N/mm². Meanwhile, on the girder, the analytical deflection value at the critical point of the middle section is 1.074 × 10⁻⁵ cm, and the results of the FEM simulation show a deflection of 1.1268 × 10⁻⁶ cm. On the end carriage section, the manual analysis results show a load of 0.4599 tons, while the FEM simulation results provide a value of 44,924 N